The diverse risk profiles of persistently absent students: Implications for attendance policies in Australia - Taylor, C; Zubrick, S; Hancock, K; Mitrou, F (My University, 2018)
The risk factors associated with absenteeism are well known. However, children's exposure to combinations of risks and how these relate to absence patterns remains unclear. Understanding variations in risk profiles among persistently non-attending children will inform the development of absence interventions. Using a longitudinal sample of Australian children (6–11 years), a latent class analysis of 19 risks identified four classes of risk exposure. Most children (56%) were exposed to minimal risk, 20% were exposed to parenting, child development, and mental health risks only, 15% were exposed to a greater extent to financial risks only, and 9% had a higher probability of exposure to all risks. Persistently non-attending children were eight times more likely to be in the high-risk group than regular attenders. However, one-third of persistent non-attenders were classified as low-risk. The heterogeneity of risk profiles is discussed in relation to policies using financial penalties to motivate improved attendance.
Journal of Education for Students Placed at Risk
Keywords: Learning, education and training; Learning, education and training